Influence of Gravel as Protection Layer on the Filter Run Time - Agustina Kiky Anggraini; Stephan Fuchs (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2020)
Abstract: Since the beginning of the usage of slow sand filter (SSF) as one of the water treat-ment technologies, studies on how to enhance the performance have been conducted to date. One of the limitations in the current knowledge is regarding the method to increase the filter run time. The addition of protection layer may extend the filter run time. This paper focuses on the influence of gravel as the protection layer to the filter run time and turbidity removal. Gravel was chosen as the material of protection layer because of its low-cost and availability. A system-atic investigation by comparing only one different factor within the filter, which was protection layer, was conducted under the laboratory scale. The experimentconsisted of two filter columns namely K1 and K2. Both filters were constructed using the same filter depth, type of sand, and grain size distribution. The protection layer was added to filter K1, but not to filter K2. The sol-ids penetration and the increase of filter head loss wasused to evaluate the filter run time. A sta-tistical analysis was also carried out to examine the difference on the turbidity removal from both filters. The findings showed that by adding the protection layer, the filter run time could be extended up to 70%. Regarding to the turbidityremoval, there was insignificant difference between two filters.